PERPETUAL AND JUST-IN-TIME INVENTORY CONTROLAPPROACHES APPLIED BY MANAGERS FOR IMPROVING OPERATIONS OF SMALL AND MEDIUM SCALE ENTERPRISES (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained the extent managers applied perpetual and just-in-time inventory approachesfor improving operations of small and medium scale enterprises in South-East Nigeria. Two researchquestions and two null hypotheses guided the study. Descriptive survey research design was adoptedfor the study. The population comprised 4745 registered SMEs managers from services, constructionand manufacturing businesses operating within South-East Nigeria. Sample size of 1424 registeredSMEs managers were used, through proportionate stratified random sampling technique. Theinstrument for data collection was a 22-item structured questionnaire. The instrument was validatedby three experts. Cronbach Alpha was used to determine the internal consistency of the instrument, with an overall co-efficient value of 0.91. Mean and standard deviation were used to answer theresearch questions, while Analysis of Variance (ANOVA) was used to test the null hypotheses at 0.05alpha levels. The findings of the study revealed that just-in-time inventory approaches is lowlyapplied by managers of SMEs in South-East, Nigeria, while perpetual inventory approaches aremoderately applied to improve their business operations. Years of business experience of managers ofSMEs significantly influence their mean ratings on the extent just-in-time inventory approaches areapplied for improving operations in South-East Nigeria; but did not significantly influence their meanratings on the extent perpetual inventory approaches are applied for improving operations. It wasrecommended among others that Management of small and medium scale enterprises should organizeregular training for managers on various inventory control approaches that will empower themtoadequately apply different inventory control approaches appropriately for busines growth, sustainability, and development.
Keywords: Perpetual and Just-In-Time Inventory Control Approaches, Managers, SMEs